Pengembangan Model Hybrid Learning pada Mata Pelajaran PJOK untuk Meningkatkan Kebugaran Jasmani dan Kemandirian Belajar Siswa Pasca Pandemi - Nur Ridwan Fauzen (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to analyze the effectiveness of Social Emotional Learning (SEL)-based physical education (PJOK) learning in reducing gadget addiction levels in elementary school students. The background of the study is based on the increasing use of gadgets that impact students' behavioral, emotional, and social aspects. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The subjects were fifth-grade students who were divided into an experimental group and a control group. The instruments used were a gadget addiction questionnaire and a learning activity observation sheet. The research procedure included a pre-test, treatment in the form of SEL-based PJOK learning, and a post-test. Data analysis techniques used paired sample t-test and independent sample t-test. The results showed a significant decrease in gadget addiction levels in the experimental group compared to the control group. These findings indicate that the integration of social and emotional aspects in PJOK learning is effective in diverting students' attention from gadget use, increasing self-control, and strengthening direct social interactions. Thus, SEL-based PJOK learning can be an innovative and relevant strategy in addressing the problem of gadget addiction in students in the digital era